Individual Pride and Collective Pride: Differences Between Chinese and American Corpora - Liu, Conghui; Li, Jing; Chen, Chuansheng; Wu, Hanlin; Yuan, Li; Yu, Guoliang (Frontiers in Psychology, 2021)
This study investigated cross-cultural differences in individual and collective pride between Chinese and Americans using data from text corpora. We found higher absolute frequencies of pride items in the American corpus than in the Chinese corpus. Cross-cultural differences were found for relative frequencies of different types of pride and some of them depended on the genre of the text corpora. For both blogs and news genres, Americans showed higher frequencies of individual pride items and lower frequencies of relational pride items than did their Chinese counterparts. Cross-cultural differences in national pride, however, depended on the genre: Chinese news genre included more national pride items than its American counterpart, but the opposite was true for the blogs genre. We discuss the implications of these results in relation to the existing literature (based on surveys and lab-based experiments) on cultural differences in individual and collective pride.